Prototipe Pemindah Wesel Kereta Menggunakan RFID Berbasis Arduino UNO - Aisyah, Siti; Winantoko, Suryo; Wibisono, Agung (LPPM Universitas Negeri Jakarta, 2017)
The prototype of railway crossing displacement using RFID based on Arduino UNO is a tool to replace mechanical transfer shippers. Components of this tool consist of RFID MFCR522, Arduino UNO, Solenoid Lock, Relay, and LCD 16x2. RFID tags will be placed next to the train body, while the RFID reader is placed on the pole before the station, its function is to detect the type of train class and enter in the path specified. Trains are programmed by the type of train class, which is economy class, executive, and business. RFID tags will tag on the RFID reader to detect train types. After that RFID reader send signal to arduino UNO. When the arduino UNO receives a signal from the RFID reader, the arduino UNO will give high input on the relay to activate the solenoid lock. Solenoid lock is used to open the train carriage. 16x2 LCDs are used as an indicator that trains are safe for roads. Economic train will cross lane 1 but if there is an executive train that will cross on line 2, then the economic train will be dismissed at the station, in order to avoid a collision. The business rail will cross line 3. Just as the economy fire, the business rail will also be stopped at the station and wait for the executive train to pass on line 2. Prototipe pemindah wesel kereta mengunakan RFID berbasis arduino uno merupakan alat untuk menggantikan sistem pemindah wesel secara mekanik. Komponen-komponen dari alat ini terdiri dari RFID MFCR522, Arduino UNO, Solenoid Lock, Relay, dan LCD 16x2. RFID tag akan di letakkan disamping badan kereta, sedangkan RFID reader di letakkan di tiang sebelum stasiun, fungsinya untuk mendeteksi jenis kelas kereta dan masuk di jalur yang telah ditentukan. Kereta diprogram berdasarkan jenis kelas kereta, yaitu kelas ekonomi, eksekutif, dan bisnis. RFID tag akan mengetag pada RFID reader untuk mendeteksi jenis kereta. Setelah itu RFID reader mengirim sinyal ke arduino UNO. Ketika arduino UNO mendapat sinyal dari RFID reader, maka arduino UNO akan memberikan input high pada relay untuk mengaktifkan solenoid lock. Solenoid lock digunakan untuk membuka wesel kereta. LCD 16x2 digunakan sebagai indikator bahwa kereta aman untuk jalan. Kereta api ekonomi akan melintasi jalur 1, akan tetapi jika ada kereta api eksekutif akan melintas di jalur 2, maka kereta api ekonomi akan diberhentikan di stasiun, agar tidak terjadi tabrakan. Kereta api bisnis akan melintasi jalur 3. Sama seperti kerta api ekonomi, kereta api bisnis juga akan dihentikan di stasiun dan menunggu kereta api eksekutif lewat di jalur 2.